Cognitive Aging is Not Created Equally: Differentiating Unique Cognitive Phenotypes in “Normal” Adults - Casaletto, Kaitlin B. (Neurobiol Aging, 2019)
Age-related cognitive decline is a public health problem, but highly diverse and difficult to predict. We captured non-overlapping cognitive phenotypes in high-functioning adults and identified baseline factors differentiating trajectories. 314 functionally normal adults (M=69y) completed 2+ visits. Participants with sample-based longitudinal slopes in memory or processing speed <−1SD were classified as “declining” on that measure. 29 and 50 individuals fell <−1SD on processing speed or memory slopes, respectively; 2.5% met criteria for both, who were excluded. At baseline, speed decliners demonstrated greater age, inflammation, and cognitive complaints compared to speed stable adults; memory decliners were more likely to be male, and had lower depressive symptoms, gray matter volumes, and white matter hyperintensities (WMH) compared to memory stable adults. Baseline speed, TNFα, and cognitive complaints accurately classified 96.3% of future speed decliners; baseline memory, sex, precuneal volume, and WMH accurately classified 88.5% of future memory decliners. There are discrete cognitive aging phenotypes reflecting non-overlapping vulnerabilities in high-functioning adults. Early markers can predict cognition even within the “normal” spectrum and underscore therapeutic targets.